Threshold of spontaneous emission amplification by relativistic electron beam in undulator - Ognivenko, V.V. (Вопросы атомной науки и техники, 2008)
Motion of a relativistic beam of electrons through an undulator is considered, with the influence of incoherent fields its spontaneous radiation on this motion being taken into aсcount. Interaction of electrons with these fields is shown to result in the increase of electron-momentum spread in the beam. The conditions of high-gain self-amplified spontaneous emission process realization in the ultrashort-wavelength FELs are discussed